Polymeric Molecular Envelope Technology for Improved Therapeutics Efficacy: A Review - Vyas, Jigar; Raytthatha, Nensi; Prajapati, Bhupendra G.; Singh, Sudarshan (Current Medicinal Chemistry, 2025)
This review explores the enhancement of therapeutic efficacy through the innovative use of polymeric molecular envelope technology (MET). It delves into the diverse methods employed to achieve superior therapeutic outcomes, shedding light on strategies for improving drug delivery and bioavailability. MET is a promising approach to improve the solubility and bioavailability of poorly water-soluble drugs. This technology involves the use of a molecular envelope of cyclic oligosaccharides called cyclodextrins, which is a supramolecular assembly of amphiphilic molecules that encapsulate and solubilize hydrophobic drug molecules. This can further improve the solubility of the drug by increasing its surface area and reducing its crystallinity. Moreover, MET also protects the drug from degradation and enhances its permeability across biological membranes. Furthermore, the review thoroughly examines the MET, including its methods of preparation, applications in drug encapsulation, and the evaluation of its potential to optimize therapeutic outcomes. By adopting current research and key findings, this review provides valuable insights into the transformative potential of polymeric molecular envelope technology for advancing the field of therapeutics.
Keywords: nanoparticles